Potential geographical distribution of Carob tree (Ceratonia siliqua L., Leguminosae) in Morocco under climate change - Jalal Kassout; Soufian Chakkour; Abdeltif El Ouahrani; Younes Hmimsa; Salama El Fatehi; Yanzheng Yan; Rachid Hadria; Mohammed Ater (African and Mediterranean Agricultural Journal - Al Awamia)
Climate change is expected to have a profound impact on the growth and distribution of plant species, particularly in Mediterranean regions. In this study, we investigate the suitable habitat and geographical distribution of Ceratonia siliqua L. (Leguminosae), an exceptional Mediterranean tree, in Morocco. Our hypothesis suggests a reduction in suitable habitats for the carob tree under climate change scenarios. To test this, we used the maximum entropy algorithm (Maxent), 303 occurrence points and 19 bioclimatic variables to generate current and future models. We considered two representative concentration pathways (RCP4.5 and RCP8.5) as future input scenarios for the years 2050 and 2070. The maximum entropy model yielded satisfactory results, with a high Area Under Curve value of 0.987 (±0.001). Jackknife tests revealed that precipitation, followed by temperature, significantly influence the biogeographical dynamics of the carob tree in Morocco. Thus, our findings confirm the projected reduction in suitable habitat area by 2050 and 2070 under climate change scenarios. The approaches developed in this study are promising for predicting the potential distribution of native Mediterranean species and can serve as an effective tool to support conservation and restoration programs.